UNDERSTANDING SERVICES IN THE ERA OF THE INTERNET OF THINGS: A SMART SERVICE TAXONOMY - Paukstadt, Ute; Strobel, Gero; Eicker, Stefan (Proceedings of the 27th European Conference on Information Systems (ECIS), 2019)
In recent years, the “Internet of Things” with so called “smart products” has obtained increasingpopularity in both practice and research. By building on the capabilities of smart products, servicestransform to “smart services” emphasizing the value smart products can provide and how it is co- created. Even though first attempts have been conducted to conceptualize and classify smart services, there seems to be no overall consensus on the specific characteristics of smart services, which different forms they can take on and how different smart services can be described. For example, existing research on smart services does not always consider the common service design elements “servicecontent” and “service delivery”. To address this shortcoming, we develop a taxonomy of smart services by applying extant literature. We further demonstrate the usefulness of our taxonomy by classifying 50 empirical objects and presenting three cases. As a contribution, the paper enhances the understanding of the notion of smart services and strengthens the conceptual foundation for future smart service research.
Keywords: Smart Services; Intelligent Services; Taxonomy; Internet of Things; Smart Products